APAKAH SEMAKIN TINGGI IPM AKAN SEMAKIN BAHAGIA? ANALISIS KLUSTER DITINJAU DARI KUALITAS PEREKONOMIAN: APAKAH SEMAKIN TINGGI IPM AKAN SEMAKIN BAHAGIA? ANALISIS KLUSTER DITINJAU DARI KUALITAS PEREKONOMIAN - Nurcholish Arifin Handoyono (AKUNTANSI DEWANTARA, 2022)
Research using cluster analysis with the K-Means test aims to determine the level of economic quality in each of Indonesia's provinces. This research also reveals whether with a high Human Development Index (HDI), the Happiness Index (HI) will also be high? The research using a quantitative approach with secondary data collected from BPS in 2021. The data consists of 34 provinces in Indonesia. The data collected are in the form of HDI, income, expenditure, percentage of formal workforce, and HI. The results show that cluster 1 contains 12 provinces with the lowest indicators on HDI, income, formal employment, but has the highest HI, cluster 2 contains 1 province with the highest indicators of HDI, income, formal employment, but has the lowest HI, and cluster 3 contains 21 provinces with indicators of HDI, income, formal employment, and IK being in the middle between clusters 1 and 2. Based on the K-means test, it can be concluded that the 4 indicators, namely HDI, income, expenditure, and the percentage of formal employment are directly proportional, but these four indicators will be inversely proportional to the HI indicator. These results assume that a high HDI is not necessarily followed by a high HI if viewed from the quality of the economy. Keyword: Development Index, Income, Expenditure, Formal Workforce, Happiness Index, Cluster Analysis